Hepatocellular nodules resulting from congenital extrahepatic portosystemic shunts can differentiate into potentially malignant hepatocellular adenomas. (3rd August 2015) - Sanada, Yukihiro; Mizuta, Koichi; Niki, Toshiro; Tashiro, Masahisa; Hirata, Yuta; Okada, Noriki; Yamada, Naoya; Ihara, Yoshiyuki; Urahashi, Taizen; Soejima, Yurie; Fukusato, Toshio; Kondo, Fukuo
Abstract Background Hepatocellular nodules caused by congenital extrahepatic portosystemic shunts (CEPS) occur as a result of abnormal portal blood flow, and are mostly cases of benign focal nodular hyperplasia (FNH). However, hepatocellular adenomas (HCA) and hepatocellular carcinomas have been documented in the CEPS patients. HCA can now be immunohistochemically diagnosed; therefore, the concept of hepatocellular nodules resulting from CEPS should be revisited. In this study, we performed a retrospective immunohistochemical investigation of hepatocellular nodules from livers isolated from the CEPS patients undergoing living donor liver transplantation (LDLT). Methods Hepatocellular nodules from livers of five patients with CEPS who underwent LDLT between June 2004 and October 2012 at our institution were immunohistochemically investigated. HCA were classified into four subtypes (HNF1α‐inactivated HCA (H‐HCA); inflammatory HCA; β‐catenin‐activated HCA (b‐HCA); unclassified HCA). Results Sixteen hepatocellular nodules were collected from livers of five patients with CEPS who underwent LDLT. Ten hepatocellular nodules were categorized as FNH (62.5%), five were categorized as b‐HCA (31.3%), and one was categorized as H‐HCA (6.2%). Conclusions Some of the hepatocellular nodules resulting from CEPS were indicative of HCAs, especially the b‐HCA subtype which has the potential for malignant transformation. Surgical or interventional treatments might have to be performed when hepatocellular nodules appear in the CEPS patients.